Safety assessment on microbial and heavy metal concentration in clarias gariepinus (African catfish) cultured in treated wastewater pond in Kumasi, Ghana - Mark, Y.A.; Amoah, Philip; Nelson, A.W.; Muspratt, A.; Aikins, S. (Informa UK Limited, 2019)
This study assesses the microbial and heavy metal distribution in African catfish (Clarias gariepinus) cultured in waste stabilization pond, and their subsequent suitability for human consumption. Treated wastewater-fed pond (WFP) was used in the culture of the fish with a non-wastewater fed pond (NWFP), fed with ground and rain water as control. Pond water, sediments and fish tissue (gill, liver, gut and skin) samples from both sources were analyzed for pathogens and heavy metal levels. Escherichia coli populations in the sediments and water from the WFP exceeded the maximum permissible limit by 2–3 log units as expected. Significantly higher levels of pathogen contamination were detected in the gut and skin of fish from the WFP than the NWFP. Heavy metal concentrations in all samples fell within the Food and Agricultural Organization (FAO)/World Health Organization (WHO) and National Oceanic and Atmospheric Administration (NOAA) permissible limits except for iron and cadmium. There were significantly higher heavy metal concentrations in gill and liver than the muscle. Even though iron recorded the highest concentrations in fish tissue, the concentrations (0.1–2.0 mg kg-1) were below the expected daily nutritional requirement (1–2 mg) for humans and pose no toxicological risk. However, catfish from WFP would require precautionary measures such as cooking/grilling prior to consumption to avoid pathogen infection.